Propafenone-Induced Cholestatic Liver Injury: When Diagnosis Does Not Skip a Beat - Ana Isabel Ferreira; Vítor Macedo Silva; Cátia Arieira; Sofia Xavier; Joana Magalhães; José Cotter (GE: Portuguese Journal of Gastroenterology)
Introduction: Propafenone is a widely used class Ic antiarrhythmic drug that is mainly metabolised by the liver. Hepatotoxicity associated with propafenone is rare, with only a few clinical cases reported in the literature. Case Presentation: We presented a case of propafenone-related hepatotoxicity, with cholestatic liver injury and development of jaundice and pruritus within 3 to 4 weeks of treatment initiation. Three months after discontinuation, the patient was asymptomatic, and all liver tests normalised. Conclusion: With this clinical case, we aimed to emphasise the importance of the medication history and the exclusion of other possible causes of altered liver enzymes.